Selected items from the Charcot-Marie-Tooth (CMT) Neuropathy Score and secondary clinical outcome measures serve as sensitive clinical markers of disease severity in CMT1A patients - Mannil, Manoj; Solari, Alessandra; Leha, Andreas; Pelayo-Negro, Ana L; Berciano, José; Schlotter-Weigel, Beate; Walter, Maggie C; Rautenstrauss, Bernd; Schnizer, Tuuli J; Schenone, Angelo; Seeman, Pavel; Kadian, Chandini; et al. (Neuromuscular disorders, 2014)
This study evaluates primary and secondary clinical outcome measures in Charcot-Marie-Tooth disease type 1A (CMT1A) with regard to their contribution towards discrimination of disease severity. The nine components of the composite Charcot-Marie-Tooth disease Neuropathy Score and six additional secondary clinical outcome measures were assessed in 479 adult patients with genetically proven CMT1A and 126 healthy controls. Using hierarchical clustering, we identified four significant clusters of patients according to clinical severity. We then tested the impact of each of the CMTNS components and of the secondary clinical parameters with regard to their power to differentiate these four clusters. The CMTNS components ulnar sensory nerve action potential (SNAP), pin sensibility, vibration and strength of arms did not increase the discriminant value of the remaining five CMTNS components (Ulnar compound motor action potential [CMAP], leg motor symptoms, arm motor symptoms, leg strength and sensory symptoms). However, three of the six additional clinical outcome measures - the 10m-timed walking test (T10MW), 9 hole-peg test (9HPT), and foot dorsal flexion dynamometry - further improved discrimination between severely and mildly affected patients. From these findings, we identified three different composite measures as score hypotheses and compared their discriminant power with that of the CMTNS. A composite of eight components CMAP, Motor symptoms legs, Motor symptoms arms, Strength of Legs, Sensory symptoms), displayed the strongest power to discriminate between the clusters. As a conclusion, five items from the CMTNS and three secondary clinical outcome measures improve the clinical assessment of patients with CMT1A significantly and are beneficial for upcoming clinical and therapeutic trials.
Keywords: Walking; Adolescent; antioxidancia; Cohort Studies; Disease Progression; Female; chůze; mladý dospělý; Male; Middle Aged; Charcot-Marie-Tooth Disease; kyselina askorbová; Muscle Strength; Young Adult; Double-Blind Method; Cluster Analysis; věkové faktory; Pain Measurement; kohortové studie; Charcotova-Marieova-Toothova nemoc; mužské pohlaví; ženské pohlaví; Adult; Age Factors; Psychomotor Performance; stupeň závažnosti nemoci; měření bolesti; hodnocení výsledků zdravotní péče; mladiství; Outcome Assessment, Health Care; dospělí; lidé středního věku; psychomotorický výkon; dvojitá slepá metoda; shluková analýza; svalová síla; Ascorbic Acid; lidé; Humans; Severity of Illness Index; Antioxidants; progrese nemoci